The Position of As-Sunnah as Evidence and Its Relevance to the Function of the Qur'an - Azzahra, Arini Nabila; Engkos Kosasih; Muhammad Al Mighwar (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to explore the position of As-Sunnah as proof in Islam and its relevance to the Quran in forming a solid religious foundation for Muslims. This research is a qualitative study with a descriptive-analytic approach to collecting and analyzing data. To support this research, researchers used data from various written sources, including books, articles, journals, and other reliable sources. The research findings show that As-Sunnah has an equal position with the Quran as proof in Islam. Both complement each other and enrich the understanding of Islam. The Quran is the main foundation of law while the As-Sunnah is a practical and concrete interpreter of the teachings of the Quran. The relevance of the functions of the Quran and As-Sunnah in the lives of Muslims is very important and has a broad impact in various aspects of life. First, Al-Quran and As-Sunnah provide moral and ethical guidelines for Muslims. Second, in Islam, the Quran and As-Sunnah occupy a central position as a legal foundation. Third, the relevance of the function of the Quran and As-Sunnah is also seen in the construction of Muslim religious identity. Fourth, authority in Muslim society is rooted in the Quran and As-Sunnah. Fifth, the relevance of the function of both is also seen in the character building of Muslim society and politics. Sixth, forming morality and social norms in Muslim society. This research also discusses the position of As-Sunnah in contemporary issues such as conceptual and functional challenges. Conceptual challenges include the development of thoughts that contradict the validity of As-Sunnah. Functional challenges include the application of As-Sunnah in contemporary social, cultural and political contexts.